ANALISIS PELAKSANAAN PEMBELAJARAN UNTUK ANAK BERKEBUTUHAN KHUSUS MELALUI PENDEKATAN LITERASI BACA-TULIS PADA KELAS RENDAH DI MI NW TANAK BEAK NARMADA - Setiani Novitasari; Iva Nurmawanti (Jurnal Perspektif Pendidikan, 2020)
The implementation of learning is constrained by the mastery of concepts by the teacher due to the limitations of teaching materials, diverse student conditions, lack of learning facilities and infrastructures. Children with special needs have obstacles in participating in in-class learning. The purpose of the study was to analyze the learning strategies undertaken by classroom teachers, the implementation of learning approaches for children with special needs with literacy, and the effectiveness of learning for children with special needs in MI NW Tanak Beak Narmada. The research approach is qualitative. The study design uses the evaluative CIPP model. Context consists of the objectives of the learning approach. Inputs include strategies that the class teacher undertakes in mastering the material, students' readiness to accept learning, and student understanding, the process focuses on the implementation of learning approaches in the classroom, and products related to student competencies in accordance with learning objectives. The results of the study concluded that the evaluation of the learning approach of children with special needs with literacy in low grades in MI NW Tanak Beak Narmada must be improved, especially for children with special needs. MI NW Tanak Beak Narmada teacher uses an integrated learning approach. The use of the learning approach is adjusted to the learning material delivered, the objectives to be achieved, and the condition of the students in the class. The effectiveness obtained during the implementation of the learning approach to learning for children with special needs with literacy is already good, with the results of the KKM score in the good category. Student characters are expected to not only be fluent in reading but also be able to understand texts that have been read